Multi-membership and effectiveness of regional trade agreements in Western and Southern Africa: a comparative study of ECOWAS and SADC - Sylvanus Kwaku Afesorgbor; Peter A.G. van Bergeijk (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Using a gravity model for 35 countries and the years 1995-2006 we estimate the impact of regional trade agreements in Africa (in particular ECOWAS and SADC) and compare this to the a benchmark of North South trade integration (Europe's preferential trade agreement). We find that - ECOWAS and SADC membership significantly increases bilateral trade flows (and by more than for example preferential trade agreements with the EU do), - SADC membership has a stronger impact compared to ECOWAS and - that the impact of multi-membership critically depends on the characteristics of the overlapping RTA We find a positive impact if an additional membership complements the integration process of the original RTA: overlapping memberships had a significant positive effect on bilateral trade within the ECOWAS bloc but it is insignificant for SADC.
Keywords: 330; Sub Sahara Africa; regional economic integration; South-South trade; North-South trade intra-regional trade; gravity model; international trade; multi-membership